Measuring currency power from 2005 to 2018 : greenback still unrivaled or increasingly constrained by its rivals? - Kotarski, Kristijan (Array, 2020)
The main research goal of this paper is to empirically assess the state of US currency power relative to its main rivals in the period between 2005 and 2018. The most novel aspect of our inquiry is the design of three new composite indices called: Monetary Capability Index (MCI), Quality of Governance Index (QGI) and Currency Internationalization Index (CII). We argue that those indices are indispensable in an attempt to empirically measure the concept of currency power, both its underlying material and non-material resources, as well as the degree of their effective exploatation. Based on the conducted analysis it is visible that material resources are a necessary but not sufficient condition to wield and exert currency power which we proxy by currency internationalization. In that regard quality of governance remains indispensable to this effort. Our measurement shows that US currency power remains unshattered by the global financial crisis (GFC) and US dollar is still placed firmly at the top of international monetary and credit hierarchy. In spite of dangers emanating from Trump’s erratic policy, US rivals either face weakening of their currency power in terms of their monetary capability or still lag far behind the US in terms of their quality of governance.